Advanced topics in learning to hash for large-scale retrieval - Huang, Long-Kai (Nanyang Technological University, 2020)
Learning to hash has become a crucial technique to analyze the dramatically increasing data engaged in machine learning or computer vision applications. As hashing methods are applied in large-scale applications, their training often faces assorted challenges from the training data such as the huge size or the data structure. This motivates our research on training-efficient hashing methods.